Application of Rasch analysis in the development and psychometric evaluation of dental undergraduates preparedness assessment scale. (19th September 2016) - Ali, K.; Slade, A.; Kay, E. J.; Zahra, D.; Chatterjee, A.; Tredwin, C.
Abstract: Aims: The aim of this study was to develop a valid and reliable scale to measure preparedness of new dental graduates. Methods: The scale development and validation was carried out using the Rasch measurement model. Following a pilot and pre‐testing of the scale, a national study was undertaken with undergraduate students from all dental schools as well as foundation dentists in UK. Results: To examine the internal validity of the scale, we conducted a Rasch analysis. External validity of the scale was checked through validation with a range of stakeholders. An excellent fit to the Rasch model provided evidence of internal construct validity. The scale demonstrated invariance, ordered thresholds and lack of differential item functioning. Unidimensionality of the scale was confirmed by independent t ‐tests. The PSI value was 0.877, indicating a good degree of person separation and internal consistency. Test–retest reliability of the scale was also established. Conclusions: The preparedness scale developed in this project reflects innovative research using a systematic approach and employment of modern psychometric methods. The scale can be used for assessment of the preparedness of undergraduate students by dental educators and potential employers as well as by the student for self‐assessment.